1974
DOI: 10.1172/jci107791
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein Synthesis and Secretion by Mucosal Biopsies of Rabbit Colon and Human Rectum

Abstract: A B S T R A C T Elucidation of mechanisms involved inthe control of colonic production of mucus requires direct examination of glycoprotein synthesis and secretion by colonic mucosa. In the past, the limited viability of intestinal mucosa in vitro has hampered such investigations. When maintained in an organ culture system, mucosal biopsies of rabbit colon and human rectum remained viable for 24 h as documented by morphologic appearance and a steady rate of protein synthesis and secretion. These biopsies also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(42 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…The thickness of mucus layer is determined by the dynamic equilibrium between secretion of mucins and its removal into the lumen [44]. For mild and moderate UC, the synthesis of secretory mucins in UC was controversially reported, showing all directions -no change [45,46], increase [47] or decrease [48] -in the cultures of tissue biopsies when compared to healthy controls. However, the thickness of the adherent mucus gel was found generally lower or unchanged [44,49], possibly due to excessive removal.…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of mucus layer is determined by the dynamic equilibrium between secretion of mucins and its removal into the lumen [44]. For mild and moderate UC, the synthesis of secretory mucins in UC was controversially reported, showing all directions -no change [45,46], increase [47] or decrease [48] -in the cultures of tissue biopsies when compared to healthy controls. However, the thickness of the adherent mucus gel was found generally lower or unchanged [44,49], possibly due to excessive removal.…”
Section: Discussionmentioning
confidence: 99%
“…MacDermott et al (25) and Neutra et al (26) have shown that cultured colonic mucosa is able to synthesize and secrete glycoproteins but little is known about alterations in this mechanism(s) in inflammatory bowel disease. In earlier studies, Kim and Isaacs (27) Specimens were obtained in the operating room within 10 min after interruption of the vascular supply and placed on ice.…”
Section: Introductionmentioning
confidence: 99%
“…Various substances such as amino acids, carbohydrates and lipids are absorbed throughout the mucous layer and the plasma membrane (10). Mucosubstances secreted from those cells differ from each other with regard to the sugar residues of the glycoprotein molecule (22,28,29).…”
mentioning
confidence: 99%